2017
DOI: 10.1097/jhq.0000000000000068
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Teamwork in the Interprofessional Bedside Rounding Process

Abstract: Patient perceptions of teamwork have been a relatively undiscovered domain. Our study investigated the use of the Patients' Insights and Views of Teamwork (PIVOT) survey on an acute cardiology unit in an academic teaching hospital with patients receiving Rounding with Heart, an interprofessional bedside rounding initiative, and others receiving traditional rounding processes. Sixty-three subjects were surveyed during their hospital stay. We found a significant difference (p = .006) in PIVOT scores between thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…The University of Kentucky Albert B. Chandler Hospital has introduced Inter-Professional Teamwork Innovation Model (ITIM) using a team to include the bedside nurse, physician, pharmacist and care-facilitator in the rounding process. Each member of the rounding team has a role and is expected to actively participate, complementing each other and providing a unified care plan [18]. Innovations such as this and other pilot programs will contribute to long-term success and grassroots change of practice which will further lead to improved outcomes for patients.…”
Section: Collaborative Care Roundsmentioning
confidence: 99%
“…The University of Kentucky Albert B. Chandler Hospital has introduced Inter-Professional Teamwork Innovation Model (ITIM) using a team to include the bedside nurse, physician, pharmacist and care-facilitator in the rounding process. Each member of the rounding team has a role and is expected to actively participate, complementing each other and providing a unified care plan [18]. Innovations such as this and other pilot programs will contribute to long-term success and grassroots change of practice which will further lead to improved outcomes for patients.…”
Section: Collaborative Care Roundsmentioning
confidence: 99%
“…(O’Leary et al, ) explored the effect of a bedside IDR on patients’ preferred and experienced role in decision‐making and activation and found no differences in these outcomes between patients receiving IDR and those that did not. (Beaird et al, ) concluded that patients exposed to IDR perceived higher levels of teamwork in their medical team compared to patients exposed to a more physician‐centric model. The results from our study support that IDR serves as an opportunity for the patient's voice to be incorporated into their care planning.…”
Section: Discussionmentioning
confidence: 99%
“…While there is support that IDR benefits practitioners, the connection to improved patient outcomes is less clear. Some studies found improvement in patient satisfaction and perceptions of teamwork with IDR (Beaird et al, 2017); (Luthy et al, 2017); (Pritts & Hiller, 2014). However, multiple studies found no change in patient outcomes with the implementation of similar practices (Cornell, Townsend-Gervis, Vardaman, & Yates, 2014); (Malec, Mork, Hoffman, & Carlson, 2017); (O'Leary et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of patient experiences of care has been identified as a “critical indicator of healthcare performance” ([53], p.17). However, Beaird et al [54] and Pomey, Ghadiri, Karazivan, Fernandez, and Clavel [43] argued that more work was needed to include patients in the team.…”
Section: Introductionmentioning
confidence: 99%